1997
DOI: 10.1021/ja963532h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Diosmacyclobutane Exchange Reactions

Abstract: Diosmacyclobutanes Os2(CO)8(olefin) undergo facile exchange reactions with olefins and acetylenes. An associative mechanism is excluded by the observation of saturation kinetics as the concentration of the entering olefin (butyl acrylate) is increased. Multivariate analysis of the rate as a function of [C2H4] (determined from solubility measurements in decane/butyl acrylate mixtures) and [butyl acrylate] suggests a stepwise mechanism in which the departing olefin migrates to a terminal position and then underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…The existence of an intermediate is necessary in order to explain the anomalous stability of 7 under conditions where the formation of the ring-opened intermediate is reversible. (As shown in Figure of the previous paper, a [BA] of 2 M is well below thatneat BA!needed to make eq 2 irreversible and its forward step rate-determining.) Any irreversible transformation of the diosmacyclobutanes 1 , 7 , and 8 should reflect the same order of ground-state stabilities observed in the mononuclear reactivity order Os(CO) 4 (ethylene) < Os(CO) 4 (propene) ( 6 ) < Os(CO) 4 ( trans -2-butene) ( 9 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The existence of an intermediate is necessary in order to explain the anomalous stability of 7 under conditions where the formation of the ring-opened intermediate is reversible. (As shown in Figure of the previous paper, a [BA] of 2 M is well below thatneat BA!needed to make eq 2 irreversible and its forward step rate-determining.) Any irreversible transformation of the diosmacyclobutanes 1 , 7 , and 8 should reflect the same order of ground-state stabilities observed in the mononuclear reactivity order Os(CO) 4 (ethylene) < Os(CO) 4 (propene) ( 6 ) < Os(CO) 4 ( trans -2-butene) ( 9 ).…”
Section: Discussionmentioning
confidence: 78%
“…Syntheses of starting materials, purification of solvents and reagents, instrumentation, and the collection and analysis of kinetic data were described in the previous paper …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectra of 1 ‘ in CD 2 Cl 2 or acetone- d 6 showed only sharp symmetrical DPOT signals at 23 °C, which were significantly broadened at −90 °C . Although we were unable to obtain well-characterizable resonances at temperatures lower than −90 °C, the spectral aspects suggest occurrence of a facile slippage of the DPOT ligands along the Pd 4 array, forming a symmetrical η 2 : η 2 : η 2 : η 2 -complex (Chart ) . It is possible that this complex, which may or may not be coordinated with solvents at the terminals of Pd 4 chain, lies as an equilibrium species with the asymmetrical form 1 ‘ or as an intermediate in the 1 H NMR symmetrization process of 1 ‘.…”
mentioning
confidence: 92%
“…We then examined the trans-olefination. Norton et al previously revealed that the reversible trans-olefination of the diosmacyclobutane complex Os 2 (μ-η 1 :η 1 -C 2 H 4 )(CO) 8 proceeds in a stereoretentive manner 36 , 37 . Our group also reported that the trans-olefination of the μ-η 3 :η 3 -1,3,5-triene Pd 2 adduct with a linear 1,3,5-triene proceeds in a stereoretentive manner 25 .…”
Section: Resultsmentioning
confidence: 99%